165 WHAT FACTORS ARE ASSOCIATED WITH ADVANCED CARE PLANNING IN COMMUNITY-DWELLING OLDER PEOPLE?. (18th November 2021) - Breslin, L; Connolly, E; Lavan, A; Kenny, R A; Briggs, R
Abstract: Background: Advance Care Planning (ACP) involves expressing wishes regarding your future medical care and/or preferences about your end-of-life in the event of serious illness. The aim of this study was to clarify the proportion of community-dwelling older people who engage in ACP and what factors are independently associated with ACP. Methods: Participants aged ≥60 years (n = 4, 831, mean age 71 years) at Wave 4 of the Irish Longitudinal Study on Ageing were asked: Have you made your wishes/preferences known about the kind of care that you would like to receive in the event of serious illness? If yes, they were asked if this had been documented informally (family/carers or medical professionals) or formally (by written advanced care plan). Logistic regression models assessed the association of covariates of interest with ACP. Results: One quarter of the study sample (1, 153/4, 831) had an ACP. Only 10% (119/1, 153) had ACP documented in writing, while only 2% (27/1, 153) had discussed ACP with a healthcare professional. Age ≥ 80 years (OR 1.63 (1.31–2.02)), female sex (OR 1.58 (1.37–1.83)), higher educational attainment (OR 1.42 (1.18–1.71), poorer self-rated health (OR 1.58 (1.04–2.39) and lower levels of religiosity (OR 1.50 (1.03–2.19) were independently associated with ACP. Conclusion: While ACP may have benefits in extending autonomy and facilitating decision-making, only 1 in 4 of this population-representative sample of older people had engaged in ACP, with only 1 in 50 having their ACP documented in writing. Further work is therefore required to educate the public and healthcare professionals regarding the benefits of ACP.